Correlation between ferromagnetic resonance and densification of RE substituted polycrystalline ferrites. Issue 11 (1st August 2018) - Manzoor, Alina; Khan, Muhammad Azhar; Kuch, Wolfgang
Abstract: We report the dopant- and size-dependent variations in high-frequency magnetic and electrical transport properties of Ho-substituted Li-Mn polycrystalline ferrites. Thermal stability and phase identification were confirmed by thermal gravimetric analysis and X-ray diffraction experiments. The overall average crystallite size decreased from 29.6 to 17.5 nm, whereas the bulk density increased from 3.47 to 4.29 g/cm 3 with increasing Ho content. Ferromagnetic resonance (FMR) measurements at the X-band revealed significant shifts in FMR linewidths and resonance positions as a function of composition. Both, FMR linewidth and porosity, were found to decrease with the systematic addition of Ho from 2538 to 2359 Oe and from 26% to 15.4%, respectively. The substitution of Ho 3+ for Fe 3+ reduced the net magnetization of the spinel lattice from 53 to 41 emu/g. Electrical measurements revealed that the resistivity is higher in samples with smaller grains possessing a greater number of thin insulating grain boundaries. The activation energy ∆ E required for hopping increases from 0.09 to 0.16 eV with Ho addition, which may be well explained by the increase in resistivity. The substitution of Ho 3+ for Fe 3+ causes a decrease in Curie temperature T c due to the damping of A-B exchange interactions.